A new ethics for a new time? : Rereading Bonhoeffer’s ‘Heritage and Decay’ - Cumaru, Luís (Stellenbosch Theological Journal, 2023)
According to Bonhoeffer, responsibility is a global response of the human being to all reality as a whole. In the fragments of his posthumous Ethics, themes such as discipleship, culture, politics, human rights, and others converge to the same point. In this article, I analyse the context in which these fragments were written and expose the reason why even under the most difficult circumstances, Bonhoeffer thought and lived life responsibly as a whole according to what Karl Barth few years earlier called Theological Existence.